Dataset for a full-year time series characterization of separately collected organic fraction of municipal solid waste from rural and urban regions in Germany - Sailer, Gregor; Eichermüller, Johanna; Poetsch, Jens; Paczkowski, Sebastian; Pelz, Stefan; Oechsner, Hans; Müller, Joachim (Data in brief, 2021)
In the municipal context and depending on the collection scheme, different waste streams are of relevance. This article contains year-round data on the chemical composition of organic fractions of municipal solid waste (OFMSW) of rural and urban origins. All samples were collected in the municipality of Tübingen, which is located in southern Germany. The sampling procedure was executed in accordance with standard procedures mentioned in the German Biowaste Ordinance. The data presented in this article include (1) sampling area and process specifications (2) organoleptic examinations (3) dry matter and organic dry matter contents (4) impurity concentrations and (5) elemental compositions (major, minor and trace elements). All datasets are presented as a time series for the year 2018. Thus, this article especially presents the influence of season and settlement structure on the physico-chemical characteristics of OFMSW. Researchers, waste management companies and municipalities can compare and expand their own OFMSW data with those presented in this article. The dataset can also be used to calculate energy yields of OFMSW when utilized in anaerobic digestion. Based on the data, it is also possible to discuss and to evaluate the material utilization of OFMSW-based digestates and compost products, especially with regard to concentrations of major, minor and trace elements. For further discussion, please refer to the original scientific article Sailer et al. (2021).